Research and Application of Cold Productivity Formula of Horizontal Well in the Power-Law Fluid Heavy Oil Reservoir - Wang, Gongchang; Liu, Yingxian; Liu, Zongbin (Frontiers in Energy Research, 2021)
Considering the rheological properties of fluid, reservoir heterogeneity, and eccentricity factor, the productivity formula of horizontal well for the power-law fluid heavy oil reservoir is derived by transforming the three-dimensional seepage problem into a two-dimensional seepage problem. The heavy oil production calculated by this formula is in good agreement with the actual production in the offshore oil field. Then, the influencing factors of production are analyzed, and the results show that the power-law index has the greatest influence on production. When the power-law index is less than 0.8, the production increases slowly with the power-law index and when it is greater than 0.8, the production increases faster. The power-law index has a greater impact on production for higher production pressure differential and longer horizontal well. Anisotropy has significant influence on the production. When the value of Kh/Kv is less than 10, the production decreases rapidly with the Kh/Kv; after the value of Kh/Kv is greater than 10, the production decreases slower. Eccentricity has trivial impact on the production.